Penyadaran Perilaku Masyarakat Terhadap Ketersediaan Produksi Tanaman Lokal Berkelanjutan di Negeri Sila Kecamatan Nusalaut Kabupaten Maluku Tengah - Alfons, Christwyn R.; Soselisa, Hermien L.; Titaley, Elsina; Frans, Jouverd F. (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The results of local terrestrial natural resources in the archipelagic region, especially indigenous communities in the Petuanan region, are superior potential that they possess as assets, both individually and collectively. This ownership has economic value to support the welfare and fulfillment of family needs, from the perspective of community tradition or culture, the potential of local natural resources as an identity and inheritance of the value of managing and utilizing the surrounding nature from ancestors in the past to the present. In fact, the meaning of inheriting these values ​​is the strategic steps taken by parents in the past to provide local food availability for the benefit of continuing the economic security of their children and grandchildren in the future. If we look closely at the goals of the ancestors in the traditional areas of Maluku, they have the view that it is the responsibility of parents to provide certainty of life for their offspring, so that they can now be seen enjoying it. As a result of this pattern of action, the community is not aware of the rejuvenation process in the context of sustainability. Sila Village, Nusalaut District, Central Maluku Regency is relatively faced with this reality, therefore efforts need to be made to create awareness in community behavior regarding the importance of maintaining the sustainability of local plants as a superior potential to support the family economy in the future. This is also a strategic step to maintain the sustainability of local crop production and regional identity.